Jahresbericht 2012 : Gemeinsam Die Globale Erholung Unterstutzen. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The IMF's 2012 Annual Report chronicles the response of the Fund's Executive Board and staff to the global financial crisis and other events during financial year 2012, which covers the period from May 1, 2011, through April 30, 2012. The print version of the Report is available in eight languages (Arabic, Chinese, English, French, German, Japanese, Russian, and Spanish), along with a CD-ROM (available in English only) that includes the Report text and ancillary materials, including the Fund's Financial Statements for FY2012.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet